A histochemical method of differentiating lower gastrointestinal tract mucin from other mucins in primary or metastatic tumours. - Culling, C F (1975)
Epithelial mucins of the normal terminal ileum, caecum, colon, and rectum of man are unique in that they alone exhibit staining following the periodate-borohydride/KOH/PAS technique. Application of this technique enables one to differentiate those mucin-producting metastases arising from adenocarcinoma of the lower gastrointestinal tract from those arising elsewhere, and may occasionally be useful in determining the site of the primary tumour when it is in doubt. Furthermore, it was found to be especially useful in distinguishing between primary adenocarcinoma of the lung and metastases in the lung from adenocarcinoma of the lower gastrointestinal tract.